Tax Reform in the Baltics, Russia, and Other Countries of the Former Soviet Union - Ebrill, Liam (Occasional Papers; Occasional Paper, 1999)
This paper provides an overview of the recent revenue performance in the Baltics, Russia, and other countries of the former Soviet Union, and a survey of these countries efforts to modify tax policy in line with the needs of increasingly market-oriented economies and to increase the effectiveness of tax administration. It focuses principally on the 12 countries of the CIS, but refers also to the Baltic countries, and addresses the period from 1995 to mid-1998, prior to the August 1998 financial crisis in Russia.